Learning to Frame Complex Sustainability Challenges in Place: Explorations Into a Transdisciplinary “Challenge Lab” Curriculum - McCrory, Gavin; Holmén, Johan; Holmberg, John; Adawi, Tom (Frontiers in Sustainability, 2021)
Complex sustainability challenges may never be fully solved, rather requiring continuous, adaptive, and reflexive responses over time. Engagement of this nature departs from well-structured problems that entail expected solutions; here, focus shifts towards ill-structured or ill-defined issues characterized by wickedness. In the context of complex challenges, inadequate or absent framing has performative implications on action. By overlooking the value of framing, eventual responses may not only fall short; they may even displace, prolong, or exacerbate situations by further entrenching unsustainability. In educational settings, we know little about how curriculum designs support challenge framing, and how students experience and learn framing processes. In this paper we explore a transdisciplinary ‘Challenge Lab’ (C-Lab) curriculum from a perspective of challenge framing. When considering framing in higher education, we turn to the agenda in education for, as and with sustainable development to be problem-solving, solutions-seeking or challenge-driven. We introduce framing as a boundary object for transformative praxis, where sustainability is held to be complex and contextual. This study is qualitative and case-based, designed to illuminate processes of and experiences into sustainability challenge framing in a transdisciplinary learning setting. Methodologically, we draw from student reflective diaries that span the duration of a curriculum design. We structure our results with the support of three consecutive lenses for understanding “curriculum”: intended, enacted, and experienced curriculum. First, we present and describe a C-Lab approach at the level of ambition and design. Here it is positioned as a student-centered space, process, and institutional configuration, working with framing and re-framing complex sustainability challenges in context. Second, we present a particular C-Lab curriculum design that unfolded in 2020. Third, we illustrate the lived experiences and practical realities of participating in C-Lab as students and as teachers. We reflect upon the dilemmas that accompany challenge framing in C-Lab, relating experiences to engineering education via the notion of depoliticization. Finally, we point towards fruitful research avenues that may extend understandings of challenge framing in higher education.